2022
DOI: 10.1590/1980-549720220018.supl.1
|View full text |Cite
|
Sign up to set email alerts
|

Environmental and occupational exposure among cancer patients in Mato Grosso, Brazil

Abstract: Objective: To estimate the prevalence of occupational and environmental exposure according to sociodemographic factors in cancer patients treated at reference hospitals in the state of Mato Grosso, Brazil. Methods: This is a cross-sectional study on cancer patients aged 18 years or older. The prevalence of exposure to pesticides, asbestos, lead, heavy metals, formaldehyde, benzene, exposure to industrial dust, and handling of other chemical substances were calculated according to sex, age group, and level of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 16 publications
0
0
0
Order By: Relevance
“…Regarding schooling, this study showed a higher prevalence of occupational exposure among participants of low education, which may consequence of not understanding or being unaware of the use of PPE and the proper handling of pesticides 36 . The data corroborate Silva et al 37 , who showed more frequent environmental and occupational exposure among participants of less education. The authors argue that such occupational exposure may be related to jobs that require less schooling and are linked to directly handling pesticides.…”
Section: Discussionsupporting
confidence: 91%
“…Regarding schooling, this study showed a higher prevalence of occupational exposure among participants of low education, which may consequence of not understanding or being unaware of the use of PPE and the proper handling of pesticides 36 . The data corroborate Silva et al 37 , who showed more frequent environmental and occupational exposure among participants of less education. The authors argue that such occupational exposure may be related to jobs that require less schooling and are linked to directly handling pesticides.…”
Section: Discussionsupporting
confidence: 91%
“…De-Assis et al 12 evidenciam a dor de cabeça entre os sintomas mais relatados. Silva et al 11 evidenciam a cefaleia como 2º sintoma mais relatado entre participantes com diagnóstico de intoxicação aguda por agrotóxicos, precedida por tontura e seguida por náusea. Em seu estudo, Oesterlund et al 10 reportaram como sintomas mais relatados a irritação da pele, dor de cabeça, cansaço extremo, sudorese excessiva, visão turva e tontura.…”
Section: Resultsunclassified
“…Silva et al 11 observou que os agrotóxicos e a poeira industrial foram as exposições de maior frequência, e que se associaram ao sexo masculino, a maiores faixas etárias e menor escolaridade. Moura et al 19 associam exposição ocupacional aos organofosforados e ao desenvolvimento de neoplasias hematológicas.…”
Section: Resultsunclassified
“…Mesmo com o resultado, as mães foram aconselhadas a continuar amamentando, pois o leite materno é o alimento ideal para crianças até os seis meses. Silva et al (2022) fizeram um estudo que estimou a prevalência de exposição ocupacional e ambiental em pacientes oncológicos, em hospitais de referência do estado de Mato Grosso. Como resultado, concluíram que um em cada cinco pacientes com câncer atendidos em hospitais de referência de Mato Grosso relatou ter sido exposto a agrotóxicos, e um a cada dez, à poeira industrial e benzeno, sendo maior a exposição entre os indivíduos do sexo masculino, mais velhos e de menor escolaridade.…”
Section: Mato Grosso: Um Dos Maiores Consumidores De Agrotóxicosunclassified